Surgery for BRCA, TP53 and PALB2: a literature review - Song, Chin Vern; Teo, Soo Hwang; Mohd Taib, Nur Aishah; Yip, Cheng Har (ecancer Global Foundation, 2018)
Introduction: The presence of a deleterious mutation, most commonly a BRCA mutation, has a tremendous impact on the management of breast cancer. We review the surgical management of BRCA mutation carriers, and two other potentially high-risk mutations, TP53 and PALB2. Methodology: A search was done on PubMed, limited to reviews and the English language only. The search terms used were 'BRCA' or 'PALB2' or 'TP53' and 'surgery'. Fifteen articles were identified by searching and one article was obtained from other sources. Results: Breast-conserving surgery has equivalent survival, but may have an increased risk of local recurrence, compared to mastectomy among BRCA mutation carriers. Contralateral prophylactic mastectomy may not improve overall survival, despite reducing the risk of developing contralateral breast cancer. The use of preoperative genetic testing allows patients to have combined curative and prophylactic surgery. However, preoperative genetic testing may influence patients to make rash decisions. In healthy BRCA mutation carriers, bilateral prophylactic mastectomy is done to prevent breast cancer from occurring. Bilateral prophylactic mastectomy is highly effective in reducing the risk of breast cancer in healthy BRCA mutation-positive women and may have a survival benefit. Prophylactic oophorectomy reduces the risk of ovarian cancer, but may not have an effect on the risk of breast cancer. There is a lack of studies on surgery for non-BRCA mutations. TP53 and PALB2 are potentially high-risk mutations for breast cancer, which may justify the use of prophylactic surgery. Advice should be given on a case-by-case basis. Conclusion: A comprehensive approach is needed to provide optimum treatment for breast cancer patients with deleterious mutations.